Optimización del proceso de corte mediante una muescadora hidráulica, para la fabricación de ductos en lámina galvanizada - Villamarín Barriga, Salomón Humberto (2017)
This research work is focused on the development and improvement of one of the processes for the formation of galvanized tol ducts for the medium and small industry specifically for A & T INTEGRAL CLIMATIZATION, which is in the line of supplying the domestic product of the country with the Ducting for mechanical ventilation and air conditioning, it has been necessary to reduce the time in the production area, due to the fact of having several dead times when making a duct, this is a process in sequence in which The research project will focus specifically on the improvement and semi-automation of the notch that is carried out in each of the galvanized tol plates and thus improve the production of this process.